Plasmon-Induced Water Splitting on Ag-Alloyed Pt Single-Atom Catalysts - Zhang, Yimin; Chen, Daqiang; Meng, Weite; Li, Shunfang; Meng, Sheng (Frontiers in Chemistry, 2021)
A promising route to realize solar-to-chemical energy conversion resorts to water splitting using plasmon photocatalysis. However, the ultrafast carrier dynamics and underlying mechanism in such processes has been seldom investigated, especially when the single-atom catalyst is introduced. Here, from the perspective of quantum dynamics at the atomic length scale and femtosecond time scale, we probe the carrier and structure dynamics of plasmon-assisted water splitting on an Ag-alloyed Pt single-atom catalyst, represented by Ag19Pt nanocluster. The substitution of an Ag atom by Pt at the tip of the tetrahedron Ag20 enhances the interaction between water and the nanoparticle. The excitation of localized surface plasmons in Ag19Pt cluster strengthens the charge separation and electron transfer upon illumination. These facts cooperatively turn on more than one charge transfer channels, and give rise to enhanced charge transfer from the metal nanoparticle to water molecule, resulting in rapid plasmon-induced water splitting. These results provide atomistic insights and guidelines for design of efficient single-atom photocatalysts for plasmon-assisted water splitting.